Epidemiological analysis of injury in Shandong Province, China - Zhang Jiyu; Xu Aiqiang; Guo Xiaolei; Ma Jixiang; Jia Chongqi (BMC, 2008)
Abstract Background Injury is an emerging public health problem with social development and modernization in developing countries. To describe the prevalence and burden of injury and provide elaborate information for policy development, we conducted a community-based household survey in the Shandong Province of China. Methods The survey was conducted in 2004. Participants were selected by a multi-stage random sampling method. Information on injuries occurring in 2003 was collected in four cities and six rural counties in Shandong Province, China. Results The estimated incidence rate of injury in Shandong Province was 67.7 per 1,000. Injury incidence was higher in rural areas (84.3 per 1,000) than in urban areas (42.9 per 1,000), and was higher among males (81.1 per 1,000) than females (54.1 per 1,000). The average years of potential life lost is 37.7 years for each fatal injury. All injuries together caused 6,080,407 RMB yuan of direct and indirect economic loss, with traffic injuries accounting for 44.8% of the total economic loss. Conclusion Injury incidence was higher among males than females, and in rural areas than in urban areas. Youngsters suffered the highest incidence of injury. Injury also caused large losses in terms of both economics and life, with traffic injuries contributing the most to this loss. Strategies for prevention of injury should be developed.